2019
DOI: 10.1016/j.vas.2019.100060
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization for glucocorticoid receptor and effect of cortisol on in vitro development of preantral follicles

Abstract: Highlights In this study, the immunolocalization for glucocorticoid receptor (NR3C1) in goat ovarian follicles and the effect of cortisol on in vitro development of preantral follicles was evaluate. The NR3C1 was strongly expressed in oocytes of primary and antral follicles. A progressive increase of immunostaining for NR3C1 in granulosa cells from primordial to antral follicles was observed. In conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
0
21
2
Order By: Relevance
“…Taken together, data collected from Ravisankar et al (2021), evidenced that glucocorticoids may play an important role during COC expansion by binding NR3C1, and that the ratio of cortisol to cortisone in follicular fluid was an accurate indicator of oocyte competence in primates [50]. These findings contradict Pontes et al (2019) who suggested that elevated cortisol concentrations were associated with a reduction in the diameter and quality of both oocytes and follicles in goats. It is possible that such discrepancies may be a result of species differences in the regulation of cortisol in pre-ovulatory follicles.…”
Section: The Effects Of Glucocorticoid Exposure On Oocyte Maturation and Early Embryonic Developmentmentioning
confidence: 84%
See 4 more Smart Citations
“…Taken together, data collected from Ravisankar et al (2021), evidenced that glucocorticoids may play an important role during COC expansion by binding NR3C1, and that the ratio of cortisol to cortisone in follicular fluid was an accurate indicator of oocyte competence in primates [50]. These findings contradict Pontes et al (2019) who suggested that elevated cortisol concentrations were associated with a reduction in the diameter and quality of both oocytes and follicles in goats. It is possible that such discrepancies may be a result of species differences in the regulation of cortisol in pre-ovulatory follicles.…”
Section: The Effects Of Glucocorticoid Exposure On Oocyte Maturation and Early Embryonic Developmentmentioning
confidence: 84%
“…Although THC may result in a temporary inhibition of psychoactive stress [ 10 ], the literature presents discrepancies regarding the effects of THC on molecular stress signaling in reproductive organs and tissues. There is evidence to suggest that both stress signaling via circulating glucocorticoids, along with THC, have significant impact on reproductive development parameters such as oocyte maturation, quality, competence, and blastocyst rates [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, there is a lack of research that explores the potential interactions between signaling pathways activated by THC and stress hormones at the level of the oocyte and embryo during early development.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations